Investigation of energy efficiency of two-way relay-assisted multi-band machine-to-machine communications - Hoang Thien Van; Vo Tien Anh; Danh Hong L.; Chi Duong Thi Kim; Hoang-Sy Nguyen (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In this paper, we improve the uplink energy efficiency (EE) of the multi-band machine-to-machine (M2M) communications underlaying cellular networks. In particular, based on the theory of stochastic geometry, we derive the closed-form expressions of the outage probability (OP), and the average energy efficiency of cellular and Machine-to-Machine users in two-way cooperative relaying networks with three-time-slot setting. We ensure the quality of service (QoS) by considering the OP and the average energy efficiency of all links. It is concluded that the three-time-slot relay-aided Machine-to-Machine communication can offer considerably high QoS and low transmission power for fairly distant machine-to-machine networks.